Bases, Stages and 'Working your Way Up': Young People's Talk about Non-Coital Practices and 'Normal' Sexual Trajectories. (February 2013) - Lewis, Ruth; Marston, Cicely; Wellings, Kaye
While the symbolic importance of 'losing your virginity' has been described in many settings, meanings of non-coital sexual experiences, such as oral sex and hand-genital contact, are often missing from theorisation of sexual transitions. Drawing on data from a qualitative mixed methods study with young people aged 16-18 in England (the 'sixteen18 project'), we explore normative expectations about non-coital sex and sexual trajectories. Our study demonstrates how gendered talk about a 'normal order' of non-coital sexual activities 'leading to' vaginal intercourse contributes to a heteronormative discourse shaping sexual narratives and experiences long before first vaginal intercourse. Pre-coital sexual experiences were accounted for in terms of providing an opportunity for young men to develop and demonstrate sexual skill, for young women to be prepared for penetration by a penis and to learn to enjoy partnered sexual encounters, and for both sexes to develop the emotional intimacy required for first vaginal intercourse in a relationship. Prior to 'having sex', young people's talk about, and experience of, non-coital sexual activities helps circulate ideas about what 'proper' sex is, which sexual practices are valued and why, which skills are required and by whom, and whose pleasure is prioritised. If sexual health programmes are to challenge gendered inequalities in dominant assumptions about sex, non-coital sexual activities should be viewed as a legitimate area for discussion.